Enhanced thermoelectric figure of merit in polycrystalline carbon nanostructures - Lehmann, Thomas; Ryndyk, Dmitry A.; Cuniberti, Gianaurelio (Giovanni) (Physical Review B - Condensed Matter and Materials Physics, 2015)
Grain boundaries are commonly observed in carbon nanostructures, but their influence on thermal and electric properties is still not completely understood. Using a combined approach of density functional tight-binding theory and nonequilibrium Green functions we investigate electron and phonon transport in carbon-based systems. In this work, quantum transport and thermoelectric properties are summarized for graphene sheets, graphene nanoribbons, and carbon nanotubes with a variety of grain boundary types in a wide temperature range. Motivated by previous findings that disorder scatters phonons more effectively than electrons, a significant improvement in the thermoelectric performance for polycrystalline systems is expected. As the effect is marginally sensitive to the grain boundary type, we demonstrate that grain boundaries are a viable tool to greatly enhance the figure of merit, paving the way for the design of new thermoelectric materials.
CRIS-Team Scopus Importer:2023-03-20